Thorax Expansion and Its Correlation to Spirometry - Agatha Narinda D. Mulyo; Vitriana Biben; Tertianto Prabowo (Indonesian Journal of Physical Medicine & Rehabilitation, 2015)
Objective: To obtain normal value of thorax expansion in relation with age, gender, body weight,and body height and also its correlation with normal values of spirometry.Methods: Values of three levels of thorax expansion were attained from 196 normal healthy subjects(aged 21-40 years old) whose spirometry results were within normal range.Results: This study revealed mean thorax expansion in level I (axilla) as 6.03 (1.44) cm, level II(4th intercostal space) 6.69 (1.43) cm and level III (xyphoid process) 6.9 (1.7) cm. Male subjectsshowed bigger value of thorax expansion. In association with spirometry, thorax expansion positivecorrelatedsignificantly with FVC (p 0.01) and FEV1 (p 0.04).Conclusion: Normal values of thorax expansion and its relations with several variables weredescribed from within 196 normal-healthy subjects. Its correlation with spirometry values showedthe ability to predict the expansion of lung from the expansion of the external thorax.Keywords: thorax expansion, spirometry